Exploring the sustainability of public housing: the case of customized public housing for artists in Seoul - Duan, Ziyu; Kim, Seiyong (Frontiers in Sustainable Cities, 2023)
Since 2014, Seoul has proposed customized public housing as a means to address the reduced effectiveness of the urban housing supply. The focus of policy has gradually shifted from total housing security to welfare support, and the South Korean government has announced that the model will be replicated nationwide by 2023.The paper aims to summarize the development and characteristics of the artist-tailored public housing through a review of policy developments and cases from 2013 to 2023. The analysis reveals that the model is characterized by a uniform supply by the public sector, starting with the rights of minority groups rather than the needs of society as a whole. It helps improve the housing supply's effectiveness and moderate the vacancy rate in the city and regional economic stagnation. Finally, this paper summarizes the staged development experience of the artist's customized public rental housing system from four aspects: housing market, supply system, regional economy, and residents' spontaneous participation, and discusses the system's role in promoting the sustainable development of the public housing system. It provides suggestions for the current model's promotion and also provides references for the binary opposition relationship between the economic value of art and urban gentrification in other countries.